Hallervorden-Spatz Disease: Case Report based on Radiological and Genetic Analytical Findings - Sardar, Ayesha; Ashfaq, Muhammad; U-Nisa, Bader-; Ahmed, Aijaz; Waseem, Hira (Journal of Liaquat University of Medical & Health Sciences, 2023)
Hallervorden-Spatz disease is a rare disorder characterized by progressive extrapyramidal dysfunction and dementia. The disease can be familial or sporadic. PKAN is inherited recessively; it has been linked to chromosome 20. A mutation in the pantothenate kinase (PANK-2) gene has been described in patients with PKAN. This case belongs to a 9-year-old girl who presented with dystonia for two years, speech disturbance and difficulty walking for the past four months. She was diagnosed based on MRI followed by genetic mutation analysis showing nonspecific PANK-2 mutation. The genetic panel of both parents was sent, which was positive for a heterozygous mutation of the PANK-2 gene in both parents. It is concluded that this variant is of uncertain significance. Keywords: Dystonia, Hallervorden-Spatz disease, Tiger-eye appearance, Movement disorder, Pantothenate kinase two deficiency.